THE FIBER CONTENT IN FIBROUS HEMP DEPENDING ON SELECTED AGROTECHNICAL FACTORS - Kryszak, N.; Chudy, M.; Konczewicz, W.; Romanowska, B.; Oleszak, G. (Plant Breeding and Seed Science, 2016)
Relationship between genotypes represented by two fibrous hemp varieties and some agrotechnical factors was investigated in the study. The aim of it was finding how selected factors (three sowing dates, two sowing densities and five harvest dates) influence on total fiber content using osmotic degumming of fibrous plants method for fiber content determination. Results showed 34% higher fiber content for Beniko in comparison to Tygra. It was also shown that fiber content in plants was stronger correlated with harvest date than date of sowing and its density.